TRABALHO RURAL: AS MARCAS DA RAÇA - Silva, Maria Aparecida De Moraes (2016)
Abstract Currently, in most Brazilian rural studies, wage labor is not part of the research topics. Moreover, in studies regarding the production of commodities by means of machines with advanced technologies, the work is hidden or even denied. Given this situation, I propose a reflection that may bring to the scene the rural workers (man and women) and uncover the racial markers that refer to the basements of the social ladder. Based on the oral history methodology of my research and on the comparative analysis of various Latin American studies, I seek to understand the permanent degradation of the rural labor situation in contemporary capitalism in the context of historical marks of coloniality.